Escola sem partido e o ataque à liberdade de ensino: a expressão do pensamento reacionário da extrema direita na educação - Brandão, Raquel Araújo Monteiro (2021)
We analyze the Escola sem Partido (EsP) movement and the attack on the freedom of teaching as a product of the Global Movement for the Reform of Education. Education is an essential social complex for managing poverty in favor of the globalization of capital. Allied to the structural crisis of capitalism is the systematic advance of the ultra-right and reactionary on a world scale as mechanisms of domination to sustain bourgeois class power. The emergence of these "new right" invokes radical elements that repel any kind of plurality and human rights, and attack democratic systems. In this sense, we investigate the modus operandi, the historical, (il)legal and conceptual trajectories of the EsP. We also investigated the mechanisms of restriction imposed on teachers in the exercise of teaching profession, the consequences for social life, the actions of legislators, and the attacks in the legal field to validate the EsP. Its most retrograde aspect is in the conception of knowledge: it deconstructs the nature and the function of the school, which is to socialize the scientific knowledge produced by humanity. In fact, it repeatedly attacks the public school management. The EsP is the materialization of the ultra-liberal doctrine represented by the logic of hegemonic financial globalization that views education as a commodity instead of a social right, configuring itself, for Brazilian ultra reactionaries, as a strategy of political and economic domination through the militarization of schools, discipline of the bodies, censorship, dismantling of educational policies, de-funding, accountability systems, corporate curriculum reforms, control and criminalization of teachers' work. Our methodological approach is dialectical and historical materialism. We used as data collection techniques the bibliographic and documental research, conducted in resolutions and judicial decisions, law proposals, and social networks, in addition to interviews with teachers. The main theoretical contributions treat about ideologies (ALTHUSSER, 1980; EAGLETON, 1997; GRAMSCI, 1977; MARX, 1996, 2004, 2012; MÉSZÁROS, 2004, 2008, 2011, 2015); education and conservatism (TOMMASELLI, 2018); gender ideology (AMORIM and SALEJ, 2016; BUGARELLI, 2020); and Escola sem Partido (FRIGOTTO, 2017; PENNA, 2018). Indeed, it is intentional to impede the capital-labor discussion and the working class understanding regarding asymmetrical power relations. For the effectiveness of omnilateral education is necessary to fight against the farce Escola sem Partido.